KEMAMPUAN BERPIKIR KRITIS MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA PEMBELAJARAN EKONOMI - Difa Zakiah Pratiwi; Nelly Sukmawati; Siti Fatimah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
PTK is research used to improve or improve the quality of learning in the classroom. This research aims to improve the critical thinking skills of class X.2 students in Economics learning through the PjBL model at SMAN 13 Palembang. The research was conducted at SMAN 13 Palembang in the even semester of the 2022-2023 academic year and involved 41 students in class X.2. Action research procedures include planning, action implementation, observation and reflection cycles. The data obtained in this research is quantitative data from the results of students' critical thinking tests during the learning process. The test results from cycle I to cycle II showed that students' critical thinking abilities increased by 16%, and critical thinking abilities increased by 12% from cycle II to cycle III and critical thinking abilities increased by 29% from cycle I to cycle III. Researchers suggest that educators can train the ability to manage information obtained by students from various learning sources in order to improve the ability to manage information in critical thinking skills.